COLLABORATIVE EFFORTS OF HEALTH ADMINISTRATORS, MANAGERS, NURSES, AND TECHNICIANS IN IMPROVING PATIENT CARE: A CROSS-SECTIONAL STUDY IN SAUDI ARABIAN HEALTHCARE FACILITIES - Saber Fadhel S. Almutairi Talal Fadhel Almutairi, Saad Moshab Aldafeeri, Abdulaziz Thamer Aldhafeeri, Abdulaziz Thani Alshammri, Dhahawi Ghunaim Aldhafeeri, Sultan Hamad Aldhafeeri (Chelonian Research Foundation, 2022)
The healthcare system in Saudi Arabia has undergone significant reforms in recent years, with a focus on improving patient care and outcomes. Effective collaboration among healthcare professionals is crucial for achieving these goals. This study aimed to explore the collaborative efforts of health administrators, managers, nurses, and technicians in improving patient care in Saudi Arabian healthcare facilities. A cross-sectional design was employed, and data were collected through semi-structured interviews with 15 healthcare professionals from various healthcare facilities in Saudi Arabia. Thematic analysis was used to analyze the data, and four main themes emerged: (1) roles and responsibilities, (2) challenges and barriers, (3) contributions to patient care, and (4) recommendations for support and empowerment. The findings highlight the essential roles these healthcare professionals play in providing quality patient care and suggest strategies for enhancing collaboration and empowering healthcare professionals to improve patient outcomes. The study provides valuable insights for policy makers and healthcare organizations in developing strategies to support and empower frontline healthcare professionals in Saudi Arabia. Keywords: collaboration, healthcare professionals, patient care, Saudi Arabia, qualitative research